Efficacy of Robusta Coffee Bean Extract (Coffea robusta) Against Bacterial Growth of Staphylococcus aureus - Muttaqin, Zulfan; Lina Hadi; Zara Maghfirah (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. This research is a study that seeks to explore the potential of robusta coffee bean extract in inhibiting the growth of Staphylococcus aureus bacteria, where this bacterium is one of the bacteria that is often found in the oral cavity and often causes infections and dental and oral problems. Methods. This research is an experimental study in vitro. Robusta coffee extract was tested at levels of 25%, 12.5%, 6.25%, and 3.125%, where each test group was tested on 6 plates of Staphylococcus aureus bacteria. Data analysis was carried out with the help of SPSS 25 software. Results. There was a significant difference in the inhibitory power of Robusta coffee extract (Coffea robusta) at concentrations of 25%, 12.5%, 6.25%, 3.125% on the growth of Staphylococcus aureus bacteria. Significant differences in inhibition were found in group I and II (p=0.002; mean diff = -0.83), group I and III (p=0.000; mean diff = -1.32), group I and IV (p= 0.000; mean diff = -2.12), group II with III (p=0.050; mean diff = -0.48), group II with IV (p=0.000; mean diff = -1.28), and group III with IV (p=0.002; mean diff = -0.80). Conclusion. Robusta coffee bean extract (Coffea robusta) has antibacterial activity against the growth of Staphylococcus aureus bacteria.